The Impact of Pulmonary Vascular Obstruction on the Risk of Recurrence of Pulmonary Embolism: A French Prospective Cohort - Orione, Charles; Tromeur, Cécile; Le Mao, Raphael; Le Floch, Pierre-Yves; Robin, Philippe; Hoffmann, Clément; Bressollette, Luc; Nonent, Michel; Le Roux, Pierre-Yves; Salaun, Pierre-Yves; Guegan, Marie; Poulhazan, Elise; Lacut, Karine; Leroyer, Christophe; Lemarié, Catherine A.; Couturaud, Francis (Thrombosis and Haemostasis, 2021)
Background We aimed to assess whether high pulmonary vascular obstruction index (PVOI) measured at the time of pulmonary embolism (PE) diagnosis is associated with an increased risk of recurrent venous thromboembolism (VTE).Study Design and Methods French prospective cohort of patients with a symptomatic episode of PE diagnosed with spiral computerized tomography pulmonary angiography (CTPA) or ventilation-perfusion (V/Q) lung scan and a follow-up of at least 6 months after anticoagulation discontinuation. PVOI was assessed based on the available diagnostic exam (V/Q lung scan or CTPA). All patients had standardized follow-up and independent clinicians adjudicated all deaths and recurrent VTE events. Main outcome was recurrent VTE after stopping anticoagulation.Results A total of 418 patients with PE were included. During a median follow-up period of 3.6 (1.2–6.0) years, 109 recurrences occurred. In multivariate analysis, PVOI ≥ 40% was an independent risk factor for recurrence (hazard ratio 1.77, 95% confidence interval 1.20–2.62, p < 0.01), whether PE was provoked by a major transient risk factor or not. A threshold at 41% was identified as the best value associated with the risk of recurrence 6 months after stopping anticoagulation (area under curve = 0.64).Conclusion PVOI ≥ 40% at PE diagnosis was an independent risk factor for recurrence VTE. Further prospective validation studies are needed.
Keywords: pulmonary embolism; deep vein thrombosis; venous thromboembolism; pulmonary vascular obstruction